CAMP sensitive nanochannels driven by conformational transition of a tripeptide-based smart polymer. Issue 23 (26th February 2020) - Ji, Shengyan; Xiong, Yuting; Lu, Wenqi; Li, Minmin; Wang, Xue; Wang, Cunli; Wang, Dongdong; Xiao, Jie; Zhu, Zhichao; Chen, Lihua; Zhang, Yahui; Qing, Guangyan
Abstract : The opening and closing of nanochannels are precisely manipulated by cAMP through globule to coil transition of smart polymer chains. Abstract : Inspired by biological nanochannels, a novel cyclic 3′, 5′-adenosine monophosphate (cAMP)-regulated artificial nanochannel based on a tripeptide Arg-Thr-Ala (RTA) design is developed. Highly specific binding between the tripeptide and cAMP triggers an obvious conformational transition of a smart polymer chain from a contracted state to a swollen one, which leads to a dynamic modulation of the gating behaviours of the nanochannels.